(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Recent studies have suggested that mycophenolate mofetil (MMF) may offer advantages over intravenous cyclophosphamide (IVC) for the treatment of lupus nephritis, but these therapies have not been compared in an international randomized, controlled trial. Here, the comparison of MMF and IVC as induction treatment for active lupus nephritis in a multinational, two-phase (induction and maintenance) study was shown in the different study. Lupus nephritis (LN) occurs in up to 60% of adults with systemic lupus erythematosus (SLE) and predicts poor survival. The prevalence of SLE and LN and treatment response vary by age, gender, location, and race/ethnicity; LN is especially common in black and Hispanic patients in the United States. MMF was at least as effective as IVC in induction treatment in previous trials in Hong Kong, Malaysia, China, and the United States. Meta-analyses of these and smaller trials suggested that MMF may offer advantages over IVC, but they have not yet been compared in an international randomized, controlled trial. Many comparative studies were undertaken in patients with LN, a two-part trial to assess the efficacy and safety of MMF as induction therapy and subsequently as maintenance therapy for LN. This article will describe the comparison of MMF with IVC, both with corticosteroids. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 63-67